From access to use of climate smart innovations; pathways that enhance uptake of climate smart innovations among smallholder farmers in Ghana - Obeng Adomaa, Faustina; Mahama, Obed Kwaku; Dalaa, Mustapha Alasan; Tepa-Yotto, Ghislain (2024)
Enhancing farmers access to and use of climate smart innovations is fundamental to building resilience into Ghana’s crop production that is largely rain-fed. This report present AICCRA Ghana's approach to developing and deploying innovation, information, financial and institutional instruments to enhance access and use of CIS-CSA innovations among smallholder farmers in Ghana. The report highlights how these instruments were integrated into the existing service delivery ecosystem as a pathway to enable farmers access and use AICCRA CIS and CSA innovation to build their climate resilience.